Combined Therapy Using Mesenchymal Stem Cells and Metal Nanoparticles: Perspectives for Ocular Injuries and Diseases - Holan, Vladimir; Javorkova, Eliska; Hermankova, Barbora; Rossner, Pavel (International journal of nanomedicine, 2025)
Stem cell-based therapy represents a promising approach for the treatment of numerous currently uncurable diseases. However, wider application of this therapy is still bound by various limitations. To increase the effectiveness of cell therapy, a combined application of stem cells with various types of chemicals or agents, which could support the immunoregulatory and therapeutic properties of stem cells, has been proposed and tested. One prospective approach is offered by the co-application of mesenchymal stem cells (MSCs), which have potent immunomodulatory and regenerative properties, and selected metal nanoparticles (NPs) which have been used in various fields of medicine for their immunomodulatory, anti-oxidant and antibacterial properties. It has been shown that the main mechanism of the therapeutic action of MSCs is the production of immunomodulatory molecules and growth factors, and that the secretory activity of MSCs can be modified by different types of NPs. For this purpose, metal NPs are extremely useful. They possess unique characteristics and can influence the growth and repair of tissues, exert strong antimicrobial activity and serve as nanocarriers. Thus, treatment based on the simultaneous application of MSCs and selected NPs combines the therapeutic effects of MSCs and impacts of NPs on applied MSCs, and on the cells and tissues of the recipient. In this review we outline the current state of studies combining the administration of MSCs and the application of metal NPs, with a focus on perspectives to use such treatment for corneal and retinal injuries and diseases.
Keywords: kombinovaná terapie; Combined Modality Therapy; combined application; Mesenchymal Stem Cell Transplantation; therapeutic effect; mesenchymal stem cells; kovové nanočástice; Metal Nanoparticles; Animals; lidé; Humans; ocular disorders; zvířata; oční nemoci; metal nanoparticles; Eye Diseases; transplantace mezenchymálních kmenových buněk; Mesenchymal Stem Cells; mezenchymální kmenové buňky